Effect of vitamin supplementation on the recovery of Ethyl Methane Sulphonate induced proteotoxicity in Anabas testudineus - Guha, Bibhas; Khuda-Bukhsh, A R (Indian Journal of Fisheries, 2011)
Effect of vitamin supplementation on the recovery of Ethyl Methane Sulphonate induced proteotoxicity in Anabas testudineus